Effects of caffeine and carbohydrate mouth rinses on repeated sprint performance - Beaven, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The beneficial effect of a carbohydrate mouth rinse (without ingestion) on exercise performance has been related to changes in brain activity (Chambers et al., 2009). Caffeine ingestion also demonstrates positive effects on exercise performance and antagonism of adenosine receptors has been identified as a possible mechanism of action (Davis & Green, 2009). However, neither the effects of carbohydrate nor caffeine mouth rinses on intermittent sprints have been examined previously. Methods: Recreationally trained males (n = 12) performed 5 x 6 s sprints on a cycle ergometer interspersed by 24 s of active recovery. Twenty-five ml of either a non-caloric placebo, 6% carbohydrate (glucose), or 1.2% caffeine solution was rinsed in the mouth for 5 s prior to each sprint in a double-blinded and balanced, cross-over design. A second trial compared a combination of carbohydrate and caffeine with a carbohydrate only mouth rinse. Post-exercise maximal heart rate and perceived exertion were recorded along with power measures. Results: Compared to the placebo, carbohydrate substantially increased initial peak power (22.1 ±19.5 W; ES: 0.81) and both caffeine (26.9 ±26.9 W; ES: 0.71) and carbohydrate (39.1 ±26.9 W; ES: 1.08) improved initial mean power. Caffeine also enhanced initial peak power performance (103.8 ±116.5 W; ES: 0.87) in a sub-group of responders (n = 6). Heart rate and rating of perceived exertion did not differ between the three trials (P > 0.05). The second trial confirmed that both carbohydrate alone and a combination of both caffeine and carbohydrate in a mouth rinse could improve initial power production in cycle sprints (ES range: 0.66 - 1.86) with the combination mouth rinse consistently out-performing the carbohydrate only condition in terms of peak (1.0 to 36.0 W) and mean power (1.0 to 35.4 W). Conclusion: Carbohydrate and/or caffeine mouth rinses rapidly increased power production in a 6 s sprint which may have positive benefits for specific short sprint exercise performance. Improvements in maximal exercise performance in the absence of fatigue resulting from a mouth rinse suggests a central mechanism that is capable of enhancing the neural drive to the motor units and access the muscle recruitment reserve proposed by Gibson and colleagues (2001).